37.0k views
1 vote
Which expressions are equivalent to 6+(-x)+2x+(-7)+2x?

Which expressions are equivalent to 6+(-x)+2x+(-7)+2x?-example-1
User Sridhar DD
by
6.6k points

1 Answer

6 votes

Answer:

x+x+6-7+x and 3-x+2x-4+2x

Explanation:

if you simplify the equation, it will be 3x-1 because you add the like terms

(6-7)+(-x+2x+2x)= (-1)+(3x)

so now you look at the equations listed and see which is simplified to 3x-1

a. (x+x+x)+(6-7)= 3x+(-1)=3x-1

b. (2x+x)+2= 3x+2

c. (3-4)+(-x+2x+2x)=(-1)+(3x)=3x-1

d. x-1

e. x+1

There were only two that resulted in 3x-1

User Achille
by
5.6k points